STUDI MODEL PEMBELAJARAN SEJARAH DI SMA TARUNA NUSANTARA - Aditya, Muhammad Fendi; Rahmadi, Darmawan (Estoria: Journal of Social Science and Humanities, 2020)
This study aims to determine : (1) Knowing the policy of principals at Taruna Nusantara High School to subjects of History, (2) Knowing the curriculum policyregarding the portion of the placement of the subjects of History, (3) howteachers deliver material and learning models History in high school of TarunaNusantara High School and Senior High School, and (4) how student opinion inHistory teachers the material. The results of the study at both schools led to thefact that Taruna Nusantara High School is promoting subjects as the history ofimportant subjects, subjects using history as a spearhead in the successfulimplementation of special curriculum-based defend the country. Especially inthe formation of character and cultivation of the spirit of nationalism, thestudents really enjoyed how the delivery of interesting material presented bythe teacher of history at this school, teachers use a good individual approach soas to maximize the potential of students.Keywords: Studies, History Learning Model